1998
DOI: 10.1159/000027879
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Are Not Effective for Otitis media with Effusion: Reanalysis of Meta-Analyses

Abstract: Objective: To determine the effectiveness of antibiotic therapy for otitis media with effusion (OME) and to examine the validity of meta-analysis for combining the results of published randomized controlled trials (RCTs) to reach generalized efficacy conclusions. Data Sources: English-language publications in refereed journals and proceedings published between 1980 and 1997, inclusive, producing 16 usable RCTs involving 2,067 children. Study Selection: RCTs evaluating the efficacy of antimicrobials for the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…46 Speculatively, this may include secondary care subgroups as an alternative to surgery, or for any antibiotic-sensitive biofilm infection, or where recurrent acute otitis media (AOM) rather than OME is deemed to be the predominant underlying pathology. 51 To conclude, with inadequate evidence for routine use of antibiotics from primary care, a number needed to treat (NNT) was estimated to be over 20, 52 and with the escalating level of threat from antibiotic resistance, antibiotics should not be recommended for routine use.…”
Section: The Evidence For Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Speculatively, this may include secondary care subgroups as an alternative to surgery, or for any antibiotic-sensitive biofilm infection, or where recurrent acute otitis media (AOM) rather than OME is deemed to be the predominant underlying pathology. 51 To conclude, with inadequate evidence for routine use of antibiotics from primary care, a number needed to treat (NNT) was estimated to be over 20, 52 and with the escalating level of threat from antibiotic resistance, antibiotics should not be recommended for routine use.…”
Section: The Evidence For Antibioticsmentioning
confidence: 99%
“…Primary care is the best setting to evaluate effectiveness of autoinflation, because most children with OME are seen in primary care and in the community, and it is increasingly clear that there are, as yet, no evidence-based treatments that work in this setting. 1,31,34,35,52,53 Lack of a good non-surgical intervention is arguably a major factor fuelling the substantial rates of inappropriate early referral for consideration of surgery, which is thus far the only proven effective treatment. 16,37 There are no known or reported harms associated with nasal autoinflation to date, with higher respiratory tract infection (RTI) rates (including AOM) noted in the control groups in two studies, making it unlikely that the increased pressure in the nose during autoinflation can spread infections, or that it acts as an object that produces cross-infection.…”
Section: The Evidence For Autoinflationmentioning
confidence: 99%
“…A meta-analysis in 1992, which accounted for the quality of RCTs and used a regression analysis, showed that antibiotic efficacy for OME is less than 2% and completely insignificant [71]. That same analysis also showed that one can always selectively choose from the published RCTs to argue for drug efficacy.…”
Section: Antibiotics For Omementioning
confidence: 99%
“…To reach a conclusion of efficacy, however, one has to exclude the two best RCTs with the largest study populations, an exclusion which cannot be ethically justified [72]. In addition to this primary RCT data, which clearly shows that antibiotics are not effective for OME, there are 6 different meta-analyses, more or less based on this dataset [71][72][73][74][75][76]. The results of those analyses range from Rosenfeld and Post [72] in 1992, claiming 23% efficacy and recommending mandatory antibiotic therapy for OME, to a Bailar [75] article in 1995 with 'nil' efficacy and which cites the article by Rosenfeld and Post [72] as an example of a seriously misleading meta-analysis.…”
Section: Antibiotics For Omementioning
confidence: 99%
“…Поздняя диагностика и несвоевременное лечение могут привести к развитию адгезивного процесса в среднем ухе, туго-ухости смешанного типа, а у детей раннего возраста -к задержке речевого развития [2,3] т. к. длительное вос-паление среднего уха приводит к формированию спаек, рубцов, дистрофических изменений [4][5][6][7][8]. Комплексное лечение ЭСО кроме санации верхних дыхательных путей включает мероприятия, направленные на восстанов-ление функций слуховой трубы, эвакуацию скопивше-гося экссудата из барабанной полости и купирование воспалительного процесса слизистой оболочки средне-го уха [9][10][11][12]. При транстубарном медикаментозном воздействии во время катетеризации слуховой трубы Обмен опытом чаще всего используют глюкокортикостероиды (декса-метазон).…”
unclassified